2005
DOI: 10.1300/j028v17n02_02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Potassium Concentration in Inland Saline Water on the Growth and Survival of the Western King Shrimp,Penaeus latisulcatusKishinouye, 1896

Abstract: The survival, growth, and condition of the western king shrimp, Penaeus latisulcatus, were measured for 42 days when grown in marine water and inland saline water with four different concentrations of potassium: 100%, 80%, 60% or 40% of the concentration of potassium in marine water (IS100, IS80, IS60, and IS40). Shrimp survival and cannibalism frequency decreased with decreasing potassium concentration, with final shrimp survival in IS100 significantly higher (P < 0.05) than in IS60 and IS40 and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 18 publications
2
41
1
Order By: Relevance
“…The necessity of fortifying potassium-deficient inland saline water to allow penaeid shrimp culture has been demonstrated by several authors (Saoud et. al., 2003;Prangnell and Fotedar, 2005;Rahman, et. al., 2005).…”
Section: Inland Saline Watermentioning
confidence: 99%
“…The necessity of fortifying potassium-deficient inland saline water to allow penaeid shrimp culture has been demonstrated by several authors (Saoud et. al., 2003;Prangnell and Fotedar, 2005;Rahman, et. al., 2005).…”
Section: Inland Saline Watermentioning
confidence: 99%
“…2005 ;Jain et al . 2006 ) and Australia Partridge & Furey 2002 ;Prangnell & Fotedar 2005, 2006aPartridge et al . 2006Tantulo & Fotedar 2006, 2007.…”
Section: Inland S Aline W Ater a Quaculture In D Ifferent C Ountriesmentioning
confidence: 99%
“…An approach to improve the survival rate of the cultured prawns is by fortifying K + in ISW through the supplementation of KCl (Rahman et al . 2005 ;Prangnell & Fotedar 2005, 2006aTantulo & Fotedar 2006 ; and also by adding 5% KCl in fi sh diets (Gong et al . 2004 ).…”
Section: Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium deficient groundwater is suitable for culture of penaeids if the water or the feed is fortified with K + [26,[44][45][46][47][48][49]. However, the benefit of feeding K + to shrimp also appears equivocal as some authors have shown that shrimp Litopenaeus vannamei reared in artificial seawater, where the [K + ] of water and feeds were varied, did not gain any substantial benefit from K + fortified feed [8].…”
Section: Introductionmentioning
confidence: 99%